A REVIEW OF NON-SOY TEMPEH AND POTENTIAL BENEFITS IN METABOLIC SYNDROME - Nafisah, Nafisah; Anjani, Gemala; Afifah, Diana Nur (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2024)
Metabolic syndrome is a medical condition that can occur due to various factors such as obesity, lack of physical activity, and genetic factors, and can lead to metabolic disorders. It can cause insulin resistance, high levels of triglycerides, low levels of high-density lipoprotein (HDL), high blood glucose levels, hypertension, and central obesity. One way to manage metabolic syndrome is through food interventions that have hypocholesterolemic effects, such as tempeh. This narrative review delves into the potential benefits of tempeh made from raw materials other than soybeans for metabolic syndrome disease. The review analyzed 13 original research articles published in the last sixteen years from Google Scholar, PubMed, and Science Direct. The findings suggest that tempeh made from non-soy ingredients like moringa seeds, quinoa seeds, barley seeds, fava beans, chickpeas, lotus seeds, and sorghum seeds contain bioactive components and nutritional content that can help reduce cholesterol levels, inflammation, oxidative stress, and blood pressure. Therefore, tempeh made from non-soy ingredients can be used as a functional food and nutraceutical to help improve the condition of metabolic syndrome. Further research on experimental animals is necessary to identify the effectiveness and mechanisms of non-soy tempeh at the molecular level against metabolic syndrome diseases.